The Role of Sleep in Maintaining Mental and Physical Health - Chakrabarty, Kamal (Journal of Community Health Provision, 2023)
This qualitative look at explores the complex relationship between sleep and intellectual and physical fitness by using examining the reports and perceptions of individuals. Through semi-dependent interviews and thematic analysis, the take a look at elucidates the multifaceted approaches in which sleep impact’s cognitive feature, emotional properly-being, and physical resilience. Participants highlighted the bidirectional relationship among sleep and mental fitness, emphasizing the want for incorporated methods to cope with sleep disturbances and psychiatric conditions. The look at additionally famous the various factors that influence sleep patterns and conduct, underscoring the importance of comprehensive interventions that don't forget person, societal, and environmental determinants.